Sosialisasi Pembuatan Pupuk Organik dari Limbah Kulit Kakao kepada para Petani di Kelurahan Tegalrejo Kabupaten Poso - Andi Wahyuni; Lilis Nuranisa; A. Muflihah Darwis; Ainun Awaliyah Tang (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Hasanuddin University presents the 107th Thematic KKN with the theme "Optimizing the Role of Unhas Community Service Students in the Community Service Program in the 2021 New Normal Period". Based on field observations that have been carried out in Tegalrejo Village, most of the people make a living as farmers, especially cocoa plants. However, the cocoa farmers only use the cocoa beans and the waste of the skin from the cocoa is left alone. Cocoa husk waste that is produced if not handled properly will be a problem for the environment. One solution that can be done to reduce cocoa waste is to make organic fertilizer from cocoa husk waste. The target of this work program is the farmers in Tegalrejo Village, Poso Regency. The method used is to make organic fertilizer directly from cocoa husk waste. The results obtained are that people know how to make organic fertilizer from cocoa waste and reduce environmental pollution due to the large amount of unused cocoa shell waste